Effects of Incubation and Rearing Temperatures on Caiman latirostris Growth - Parachu Marco, Maria Virginia (2010)
Different studies found that incubation temperature has an influence on the size of Caiman latirostris hatchlings and determines their gonadal sex. Experimental manipulations revealed that the effects of temperature on growth are independent of sex. Ambient temperature after hatching is also an influential factor: juvenile caiman had lower growth at a cool (29°C) vs. a warm temperature (33°C) independent of incubation temperatures. Two-month-old caiman were raised at 2 different temperatures (29 and 33°C) for 100 d. These animals were subjected to different incubation treatments: 29, 31 (females), 33 (males), and 33°C with 17β-estradiol (females). No differences were found in growth based on incubation temperature or sex. Our data indicate that the evolutionary advantage of a temperature-dependent sex determination, if it exists, is not bound to differential growth between the sexes nor to incubation temperature, at least in the 1st stages of life before hatchlings reach their 1st winter. Temperatures during the development and grow-out phases have direct effects on the size of the broad-snouted caiman.